Analysis of Influence Internal Locus of Control Toward Opportunity Recognition Through Entrepreneurial Intention - Nizar Alam Hamdani; Mohamad Refi Alamsyah Al Jauzi; Isnawati, Isnawati; Intan Permana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Opportunity recognition is an idea that individuals can implement in finding a business concept. The agricultural and industrial sector has the lowest growth in recent years compared to other industrial sectors. This research aims to improve the ability to analyze business opportunities with entrepreneurial intention and self-control to build a business in the future. Researchers surveyed 708 people via email and face-to-face interaction. Seventy-five respondents provided varying ratings. The response rate was 84%. The instrument used to conduct the research was a questionnaire with Likert scale statements. It was distributed both online and in person. The data was analyzed using structural equation modeling (SEM). The research results were accurate and reliable, with a significance level of 95%. This research concludes that the internal locus of control influences opportunity recognition through entrepreneurial intention. This research shows that having an internal locus of control, entrepreneurial intention, and the ability to analyze potential opportunities play a crucial role in business development.